Large Enrichment of Anthropogenic Organic Matter Degrading Bacteria in the Sea-Surface Microlayer at Coastal Livingston Island (Antarctica) - Martinez-Varela, Alícia; Casas, Gemma; Piña, Benjamin; Dachs, Jordi; Vila-Costa, Maria (Frontiers in Microbiology, 2020)
The composition of bacteria inhabiting the sea-surface microlayer (SML) is poorly characterized and yet undescribed for the Southern Ocean, despite their relevance for the biogeochemistry of the surface ocean. We report the abundances and microbial diversity of bacteria inhabiting the SML and the subsurface waters (SSL) determined from a unique sample set from a polar coastal ecosystem (Livingston Island, Antarctica). From early to late austral summer (January-March 2018), we consistently found a higher abundance of bacteria in the SML than in the SSL. The SML was  enriched in some Gammaproteobacteria taxa known to degrade a wide range of semivolatile, hydrophobic, and surfactant-like organic pollutants. Hydrocarbons and other synthetic chemicals including surfactants, such as perfluooroalkyl substances (PFAS), reach remote marine environments by atmospheric transport and deposition and by oceanic currents,  and are known to accumulate in the SML.  Relative abundances of specific SML-enriched bacterial groups were significantly correlated to concentrations of PFASs, taken as a proxy of hydrophobic anthropogenic pollutants present in the SML and its stability. Our observations provide evidence for an important pollutant-bacteria interaction in the marine SML. Given that pollutant emissions have increased during the Anthropocene, our results point to the need to assess chemical pollution as a factor modulating marine microbiomes in the contemporaneous and future oceans.